Towards a Finalist Conception of the Concession Contract - Carneiro Echevarría, Max (2015)
This article analyzes the need to adopt a strictly contractual vision of the concession contract, that limits the discretionary actions of the State, in order to allow legal framework permit the development of infraestructure for public use.